Manipulationen in der Transplantationsmedizin: ein Fall von organisationaler Devianz? - Pohlmann, Markus; Höly, Kristina (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2017)
In recent years, the frequent manipulation of the waiting lists for an organ transplant by physicians caused a stir in Germany. This article deals with the question of how to explain these manipulations. It does so, by analyzing court records, audit reports and interviews. The authors make a case for applying the theoretical perspective of organizational deviance, and they examine empirically to what extent the individual and/or organizational deviance accounts for the manipulations. To this end, they combine the content analysis of structural data with the collective mindset analysis of interview data, which links the deviant behavior to the rules that guide cognition and action in this particular field. They conclude that the frequency and nature of the manipulations indicates an organized action that was established due to the medical competitive pressure, the tight hierarchies of authority and expertise, and the socialization of the pioneers in an innovative field of medicine. According to present knowledge, neither personal enrichment nor criminal energy was necessary to manipulate. This form of organizational and “professional” deviance may instead be explained by organizational incentive structures and the dominance of professional autonomy and reputation. Thus, it differs significantly from economic crime, because the economic benefits only play a minor role. Instead, the tragic choice situation that is structured by the relative scarcity of organs implies that in both cases, be it regulatory compliance or organizational deviance, certain patients die.
Gesehen am 11.05.2018